KAJIAN IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI (SMKK) PADA KONTRAKTOR DI KOTA BANDAR LAMPUNG - Zhafira, Elian; Yuliyanto, Andry; Sitepu, Arif Rahman Hakim; Simanjuntak, Indi Rezki Uli; Sihombing, Tera Melya Patrice; P., Kirtinanda; S., Andi (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
The Construction Safety Management System (SMKK) reduces work accident rates in the construction industry. Data grouping on construction companies implementing SMKK can provide information regarding its implementation to small and medium contractors in Bandar Lampung. This research uses a quantitative method through a questionnaire. It is statistically processed to obtain the percentage of SMKK implementation and a qualitative method by reviewing based on the Ministerial Regulation of Public Works and Housing Number 10 of 2021, other regulations, and previous research. SMKK contains several indicators: leadership and labor participation, construction safety planning, construction safety support, construction safety operations, and performance evaluation. Evaluation of the implementation of SMKK for small and medium contractors in Bandar Lampung shows that, on average, 49.1% of all indicators still need to be adequately implemented for small contractors. Meanwhile, an average of 61.7% for medium-sized contractors indicates that all indicators have been appropriately implemented. The outcome of this study was concluded with the recommendation that small and medium contractors should conduct SMKK training socialization to increase workers's knowledge, skills, and competencies in implementing SMKK in the construction field.